1992
DOI: 10.1557/jmr.1992.2429
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of diamond on carbon-implanted single crystal copper surfaces

Abstract: The nucleation and growth of diamond crystals on single crystal copper surfaces has been studied. Microwave plasma enhanced chemical vapor deposition (MPECVD) was used for diamond nucleation and growth. Prior to diamond nucleation, the single crystal copper surface is modified by carbon ion implantation at an elevated temperature (~820 °C). This procedure leads to the formation of a graphite film on the copper surface, resulting in an enhancement of diamond crystallite nucleation. A simple lattice model has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The deposit subsequently disappeared, and the final deposit contained only polycrystalline diamond. Several other experiments on Ni and Pt in HFCVD [17], on Si [19] and Cu [32,34,62] in MW PACVD have also provided direct evidence for the formation of graphite on the substrates prior to diamond nucleation. It was found that the graphite film formed initially on the substrate surface greatly enhanced diamond nucleation [32,34].…”
Section: Nucleation On An Intermediate Layer Of Graphitementioning
confidence: 87%
See 4 more Smart Citations
“…The deposit subsequently disappeared, and the final deposit contained only polycrystalline diamond. Several other experiments on Ni and Pt in HFCVD [17], on Si [19] and Cu [32,34,62] in MW PACVD have also provided direct evidence for the formation of graphite on the substrates prior to diamond nucleation. It was found that the graphite film formed initially on the substrate surface greatly enhanced diamond nucleation [32,34].…”
Section: Nucleation On An Intermediate Layer Of Graphitementioning
confidence: 87%
“…Volmer-Weber 3-D island growth [58] is the mode of nucleation and growth of polycrystalline diamond films directly on non-diamond substrates due to the highest surface energies of diamond among any known materials (see Tables 3 and 4 Diamond nucleation on non-diamond substrates is generally proposed to occur mostly on an intermediate layer of diamond-like amorphous carbon [9][10][11]30,35,61], metal carbides [12,14,16,22,23,25,28,29,40,[62][63][64][65][66][67][68][69][70], or graphite [13,17,19,32,34,62,71] formed at the substrate surface due to chemical interactions between activated gas species and the surface during the incubation period. Such intermediate layers provide nucleation sites for diamond crystallite growth [9,17,70], and hence enhance diamond nucleation densities on non-diamond substrates [21,37,70,71] and offer an opportunity for controlling the morphology [21,37], orientation and texture [28,<...>…”
Section: Surface Nucleationmentioning
confidence: 99%
See 3 more Smart Citations